Anion triggered metallogels: demetalation and crystal growth inside the gel matrix and improvement in viscoelastic properties using Au-NPs. Issue 12 (7th March 2016) - Biswas, Arnab; Dubey, Mrigendra; Mukhopadhyay, Sujay; Kumar, Ashish; Pandey, Daya Shankar
Abstract : Progelator Zn-TRPA-2 undergoes Cl − triggered gelation to afford ZTP2G. Zn-TRPA-2 capped Au-NPs under similar conditions afforded composite metallogel GNZTP2G with superior viscoelastic properties. Again Cl − and NO3 − simultaneously grew demetalated crystals inside ZTP2G matrix. Abstract : Progelator complex Zn-TRPA-2 undergoes Cl − triggered gelation to afford ZTP2G, while Zn-TRPA-2 capped Au-NPs under similar conditions gave another gel GNZTP2G which also represents a rare nano-composite metallogel. When Zn-TRPA-2 was triggered by Cl − and NO3 − simultaneously, crystals of demetalated species NA-TRPA-2 grew inside the ZTP2G matrix. Interestingly, GNZTP2G exhibits superior viscoelastic properties over ZTP2G.